2017
DOI: 10.1136/bjsports-2017-098135
|View full text |Cite
|
Sign up to set email alerts
|

Tackler’s head position relative to the ball carrier is highly correlated with head and neck injuries in rugby

Abstract: ObjectivesTo characterise the tackler’s head position during one-on-one tackling in rugby and to determine the incidence of head, neck and shoulder injuries through analysis of game videos, injury records and a questionnaire completed by the tacklers themselves.MethodsWe randomly selected 28 game videos featuring two university teams in competitions held in 2015 and 2016. Tackles were categorised according to tackler’s head position. The ‘pre-contact phase’ was defined; its duration and the number of steps tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
4
22
0
2
Order By: Relevance
“…These findings are in line with the results of previous research on the characteristics of tackles based on video records in rugby union. 7,11,12,19 However, the confidence intervals of these characteristics were fairly wide. It is considered that the numbers within the subgroup, tackles with or without a concussion, were not drastically different in comparison to that for other characteristics, and thus, the standard error was large.…”
Section: Factors Increasing the Likelihood Of The Tackler-related Cmentioning
confidence: 99%
“…These findings are in line with the results of previous research on the characteristics of tackles based on video records in rugby union. 7,11,12,19 However, the confidence intervals of these characteristics were fairly wide. It is considered that the numbers within the subgroup, tackles with or without a concussion, were not drastically different in comparison to that for other characteristics, and thus, the standard error was large.…”
Section: Factors Increasing the Likelihood Of The Tackler-related Cmentioning
confidence: 99%
“…Therefore, tacklers should initially contact the ball-carrier with their shoulder to prevent concussion in comparison to initially contacting with their head/neck. In addition, Sobue et al reported that concussion for tacklers occurred significantly more often during tackles with incorrect head positioning 18) . Our result concurs with the previous study (Table 4) 18) .…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…In addition, Sobue et al reported that concussion for tacklers occurred significantly more often during tackles with incorrect head positioning 18) . Our result concurs with the previous study (Table 4) 18) . However, using multiple logistic regression analysis, we did not find that a tackler had a significant risk of concussion when his head was in front of the ball-carrier.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 2 more Smart Citations